A Case Report of Leukocytosis During Modified Electroconvulsive Therapy of Paranoid Personality Disorder - Mu, Xingyu; Xu, Jiao; Lin, Peilin; Luo, Ya; Zhu, Yuan; Shi, Yi; Chen, Shangtao; Wu, Zengxiang; Li, Shuangqing (Frontiers in Psychiatry, 2022)
Introduction: Modified electric convulsive treatment (MECT) is a viable therapeutic option for patients with mood disorders and schizophrenia. We found that there is a relationship between MECT and leukocytosis. To the best of our knowledge, this is the first case of this problem. There are no relevant guidelines recommending the risk of leukocytosis caused by MCET or to reduce the risk or method. We hope to share this case to provide a reference for the prevention and treatment of similar patients with leukocytosis during or after MECT and remind psychiatrists to pay attention to this risk of leukocytosis before making the decision of MECT while knowing how to deal with it. Case presentation: We describe a case of a 24-year-old young woman diagnosed with PPD whose symptoms began at 19 years old. Her main clinical manifestations are feeling targeted, cheated, tracked, misunderstood, and repeating action. Since antipsychotic treatment was ineffective, we considered MECT. After MECT, the patient's body temperature increased, and leukocytosis was found. After excluding infection and other possibilities, we added 1000 ml physiological saline to the patient through the vein. The white blood cell (WBC) count returned to normal in a short time. Conclusion: Before MECT treatment, it is necessary for us to screen blood cytology. During and after MECT, we should be alert to leukocytosis that may be related to MECT and deal with it correctly in time.